DDR in Ongoing Conflicts: Lessons from the National DDR Gender Strategy in Cameroon (African Journal of Law and Politics, 2025)
The role of gender in peacebuilding and Disarmament, Demobilization, and Reintegration (DDR) is paramount yet often underexplored. The complex dynamics of the Boko Haram insurgency in Cameroon’s Far North Region and the subsequent DDR programme is a good case. Existing literature predominantly frames women as victims, overlooking their agency and contributions, particularly in community-based DDR efforts. This paper seeks to address this research gap by examining the active participation of women’s organisations (WOs) in supporting the implementation of the National DDR Gender Strategy across four heavily impacted Divisions of the Far North Region: Mayo-Sava, Mayo-Tsanaga, Logone-et-Chari, and Diamare. Utilizing a qualitative approach, the study conducts in-depth interviews and a focus group discussion with representatives from WOs, coupled with documentary analysis to capture their experiences and strategies. Key findings indicate that WOs have emerged as vital actors in mobilizing community acceptance of ex-combatants, fostering dialogue, and enhancing women's leadership roles within the DDR process. Despite the positive shifts in community attitudes, WOs face significant challenges, including stigma, resource constraints, and socio-economic barriers that impede their effectiveness. The implications of this study buttress the necessity of integrating gender-sensitive approaches into DDR initiatives, emphasizing the importance of women's voices in policy formulation. Furthermore, it advocates for sustainable partnerships among stakeholders to improve DDR outcomes in contexts afflicted by violent extremism.